First report of Downy Mildew caused by peronospora belbahrii on sweet basil (Ocimum basilicum) in Cyprus - Kanetis, Loukas; Vasiliou, A.; Neophytou, G.; Samouel, S.; Tsaltas, Dimitrios (My University, 2014)
Sweet basil (Ocimum basilicum L.) is an economically important annual aromatic plant, grown mostly for culinary use for both fresh and dry consumption and as a source of essential oil. In Cyprus, approximately 4 ha are grown annually, either in greenhouses as a year-round crop or in open fields from April to November, and the majority of the production is exported to the European market. During May 2012, a sweet basil cv. Genovese Gigante greenhouse operation in the area of Limassol was severely affected by a foliar disease, causing almost 100% crop losses. Within a few days, a similar, heavy disease incidence was also reported from a nearby greenhouse facility on the Genovese-type cultivars Superbo, Aroma 2, and Bonazza, as well as on Thai basil (O. basilicum var. thyrsiflorum). Successively, destructive hits of similar symptomatology have been reported from other areas and since then the disease appears to have been well-established in the country, causing major economic damages. It is also noteworthy to mention that in greenhouse infections the disease remains active even during winter, considering the mild environmental conditions and the monoculture fashion followed. Symptoms appeared on the leaves initially as interveinal, zonal, chlorotic lesions, followed by the appearance of a fuzzy, purplish sporulation on the abaxial side. Progressively, infected leaves curled and sporadic necrotic spots were evident and finally abscised. Light microscopic examination of infected samples revealed the presence of straight, hyaline sporangiophores (n = 15) typical of downy mildew, 210 to 590 μm long (mean = 350.7 μm; SD ± 117.5 μm) × 12 to 15 μm wide (mean = 13.1 μm; SD ± 1.4 μm). Sporangiophores were monopodially branched three to five times, terminating with curved branchlets bearing single sporangia at their tips. The sporangia (n = 25) were purplish-grey, ovoid to subglobose, and measured 32 to 22 μm in length (mean = 27.2 μm; SD ± 2.8 μm) and 30 to 10 μm in breadth (mean = 21.7 μm; SD ± 4.8 μm). Based on these morphological characteristics, the causal agent was identified as Peronospora belbahrii Thines (1,4). Furthermore, genomic DNA was extracted from infected plant tissue from eight different samples according to Dellaporta et al. (2). The complete ITS rDNA region was amplified and sequenced using primers ITS5 and ITS4 (3). Two of the consensus sequences were deposited in GenBank (Accession Nos. KF419289 and KF419290) and a BLAST analysis in the NCBI database revealed 99% similarity to all of the P. belbahrii sequences and other Peronospora sp. previously reported on sweet basil (Accession Nos. AY831719, DQ479408, FJ394336, and FJ436024). In a pathogenicity trial, five 40-day-old potted sweet basil plants were spray-inoculated with a sporangial suspension (1 × 105 sporangia/ml) until runoff, bagged for 24 h, and placed in a growth chamber at 18°C. Subsequently, the plastic bags were removed and the plants were kept at 22°C with a 16-h photoperiod and 80% relative humidity. Additionally, five plants were water-sprayed and served as controls. Typical downy mildew symptoms appeared 6 to 8 days after inoculation, while the uninoculated plants remained disease-free. To our knowledge, this is first report of downy mildew on sweet basil in Cyprus.
Keywords: Basil; Peronospora belbahrii; Ocimum basilicum